Protesty 17 czerwca 1953 roku w polityce i pamięci niemieckiej - przyczynek do obchodów 60. Rocznicy czerwca'53 = The protests of 17 june 1953 in the german politics and remembrance - a contribution to the celebration of the 60th anniversary of "June 1953" - Świder, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is not only the causes of the protests of 17 June 1953, which took place in the German Democratic Republic, but also commemoration of those events over the space of the last 60 years that varied greatly. Those events have been written on a permanent basis into not only the German politics, but the German memory as well, becoming a subject of political discussions.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia